2014
DOI: 10.3389/fncel.2014.00415
|View full text |Cite
|
Sign up to set email alerts
|

GABA-A and NMDA receptor subunit mRNA expression is altered in the caudate but not the putamen of the postmortem brains of alcoholics

Abstract: Chronic consumption of alcohol by humans has been shown to lead to impairment of executive and cognitive functions. Here, we have studied the mRNA expression of ion channel receptors for glutamate and GABA in the dorsal striatum of post-mortem brains from alcoholics (n = 29) and normal controls (n = 29), with the focus on the caudate nucleus that is associated with the frontal cortex executive functions and automatic thinking and on the putamen area that is linked to motor cortices and automatic movements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
(129 reference statements)
1
20
0
Order By: Relevance
“…For the most part, these studies have generally supported the animal work demonstrating an up-regulation in glutamate receptors following chronic alcohol exposure (Breese et al, 1995; Jin et al, 2014b; Enoch et al, 2014; Bhandage et al, 2014; Laukkanen et al, 2015). Together with the animal studies described above, these data suggest that glutamatergic alterations within these regions likely plays a role in the impaired cognitive function and the transition from goal-direct to habitual behavior that is characteristic of alcohol addiction.…”
Section: Glutamatergic Adaptations Involved In Dependence-induced mentioning
confidence: 68%
See 1 more Smart Citation
“…For the most part, these studies have generally supported the animal work demonstrating an up-regulation in glutamate receptors following chronic alcohol exposure (Breese et al, 1995; Jin et al, 2014b; Enoch et al, 2014; Bhandage et al, 2014; Laukkanen et al, 2015). Together with the animal studies described above, these data suggest that glutamatergic alterations within these regions likely plays a role in the impaired cognitive function and the transition from goal-direct to habitual behavior that is characteristic of alcohol addiction.…”
Section: Glutamatergic Adaptations Involved In Dependence-induced mentioning
confidence: 68%
“…In fact, withdrawal from alcohol is associated with increased glutamate concentration in both humans and rodents (Hermann et al, 2012) and severity of alcohol dependence is positively correlated with CSF glutamate (Umhau et al, 2010). Furthermore, a growing body of literature is emerging indicating that significant glutamatergic adaptations occur in brain regions underlying reward, cognition, and affect in alcohol-dependent individuals (Jin et al, 2014a, 2014b; Enoch et al, 2014; Bhandage et al, 2014; Laukkanen et al, 2015). While human studies are critical to our understanding of the neuroadaptive processes that occur in addicted individuals, animal models have been essential to our appreciation of the cellular adaptations that occur within the neural circuits underlying dependence-induced symptomology, which may help to uncover pharmacological targets for the treatment of alcoholism.…”
Section: Overview Of Glutamate Receptorsmentioning
confidence: 99%
“…The same situation was found for other drugs of abuse (Albertson et al, 2004(Albertson et al, , 2006. Significant alterations in glutamate and GABA receptor mRNAs were found in postmortem brains of alcohol-dependent subjects, but the changes differed from one brain region to another (Jin et al, 2011(Jin et al, , 2014aBhandage et al, 2014). For these obvious reasons, we reviewed the literature for each drug according to the specific brain regions where alterations have been observed most commonly in preclinical experiments.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, the changes were dependent on the length of ethanol exposure. Recent data from human postmortem brain areas from controls and alcoholics have also revealed brain region-specific changes in GABA A and glutamate receptor subunit expression in alcoholics (Jin et al, 2011;Bhandage et al, 2014;Jin et al, 2014a,b).…”
Section: +mentioning
confidence: 99%
“…Jin et al demonstrated that mRNA expressions of AMPA receptor subunits were lower in the central amygdala (n = 9) and higher in the hippocampus dentate gyrus (n = 13) in the patient group, while there were no differences in the dorsolateral prefrontal cortex (DLPFC) (n = 14) or the orbitofrontal cortex (OFC) (n = 11). Bhandage et al found that mRNAs expression levels were not different among any of the glutamate receptor subunits in the caudate and the putamen (n = 29). Farris et al showed higher gene connectivity including GRIA1 in the prefrontal cortex (n = 16).…”
Section: Alcohol Use Disordermentioning
confidence: 97%